1988
DOI: 10.1067/mva.1988.avs0070420
|View full text |Cite
|
Sign up to set email alerts
|

In vitro bursting strength studies of laser-welded tissue and comparison with conventional anastomosis

Abstract: We compared the mechanical integrity of microvascular anastomoses created with a carbon dioxide (CO2) laser with conventional suture anastomoses. Seventy rat femoral artery segments (35 lased and 35 sutured) were harvested at 1, 24, and 72 hours, and 1, 3, 6, and 12 weeks postoperatively. These segments were subjected to increasingly higher in vitro intraluminal hydrostatic pressures (bursting pressure). Conventionally sutured anastomoses exhibited significantly increased ability (p less than 0.05) to withstan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1989
1989
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…The leaking point pressure ͑LPP͒ was measured directly after laser irradiation ͑two passes: n =15; three passes: n =5͒ in accordance with the method of Basu et al 18 and Fahner et al 19 One end of the laser-treated carotid segment was sealed by ligation and the vessel lumen filled with methylene blue dye ͑Sigma-Aldrich͒. The other end was ligated around a blunt 25G needle that was connected to a rate-controlled syringe infusion pump and a pressure controller ͑Braun Medical, Melsungen, Germany͒ through an interposed T-valve.…”
Section: Leaking Point Pressurementioning
confidence: 99%
“…The leaking point pressure ͑LPP͒ was measured directly after laser irradiation ͑two passes: n =15; three passes: n =5͒ in accordance with the method of Basu et al 18 and Fahner et al 19 One end of the laser-treated carotid segment was sealed by ligation and the vessel lumen filled with methylene blue dye ͑Sigma-Aldrich͒. The other end was ligated around a blunt 25G needle that was connected to a rate-controlled syringe infusion pump and a pressure controller ͑Braun Medical, Melsungen, Germany͒ through an interposed T-valve.…”
Section: Leaking Point Pressurementioning
confidence: 99%
“…The major concern with laser techniques is the strength of the repair and its ability to avoid dehiscence and aneurysm formation. 15 We used our new technique 10 for in vivo burst testing to determine the relative strengths of a conventional laser technique versus a conventional suture and conventional telescopic technique. Our data demonstrate that the laser technique is modestly weaker than the other techniques at each stage of healing.…”
Section: Discussionmentioning
confidence: 99%
“…Laser-welding for vascular anastomosis has been applied and investigated by a number of authors. 2 -47 - 9 The majority used 3 to 4 stay sutures to adapt to the vessel walls. 4 -' 01314 Others inserted an absorbable stent for precise endothelial apposition.…”
Section: Discussionmentioning
confidence: 99%
“…34 Studies of tensile and bursting strength have shown that LAMA can consistently withstand supra-physiologic pressures, although there is a marked weakness in bursting and tensile strength at three days postoperatively. 5 - 9 Laser welding seems to be especially advantageous in traumatized blood vessels, probably due to a reduction of foreign-body reaction, because fewer sutures are needed for LAMA. 10 Completely laser-welded anastomoses would thus be desirable, as they promise the greatest saving in time, the easiest operative performance, and no foreign-body reaction.…”
mentioning
confidence: 99%